Jacek Przygodzki, Rada Najwyższa Tymczasowa Księstwa Warszawskiego 1813-1815, 2002 - Krzymkowski, Marek (Czasopismo Prawno-Historyczne, 2005)
Jacek Przygodzki, Rada Najwyższa Tymczasowa Księstwa Warszawskiego 1813-1815. Organizacja i działalność. Wydawnictwo Uniwersytetu Wrocławskiego, Wrocław 2002, ss. 281.